Self-confidence as a predictor of digital skills: a fundamental pillar for the digitalization of higher education - Rosales-Márquez, Cinthia; Carbonell-García, Carmen Elena; Miranda-Vargas, Víctor; Diaz-Zavala, Rocio; Laura-De La Cruz, Kevin Mario (Frontiers in Education, 2025)
Contemporary higher education must prepare students for a digital world by equipping them with both technical and critical competencies. In this context, self-confidence is key, as believing in oneself facilitates the acquisition and use of digital tools. This research aims to examine the role of self-confidence as a predictor of digital competency development among university students in Peru. A mixed-approach was employed, utilizing predictive calculations on one hand, alongside quantitative data collection and analysis through interviews. The sample consisted of 213 postgraduate students from various regions of Peru, along with 20 university professors at the postgraduate level. The study's findings confirm that self-confidence is a significant predictor of the development of digital skills in Peruvian university students. A moderate positive correlation (r = 0.484, p < 0.001) was identified between the two variables, indicating that students with higher levels of self-confidence are more likely to develop advanced digital skills. These results are further reinforced by qualitative analysis, as the digitalization of education cannot be contemplated with students who lack digital skills.